The role of the nurse in the immediate postoperative period of cardiac surgeries: An integrative review (Research, Society and Development, 2026)
According to data from the World Health Organization, cardiovascular diseases are the leading cause of death worldwide. They often require highly complex cardiac surgery, which demands specific care in the immediate postoperative period, especially in the Intensive Care Unit, considering the changes in the body caused during the procedures. In this context, the role of the nurse is essential to ensure the patient's clinical stability and prevent complications. The objective of this study is to identify the role of nurses in caring for adult patients in the immediate postoperative period of cardiac surgery in the Intensive Care Unit. This is an integrative review study. The search for scientific articles was carried out in the Scielo, PubMed, and Lilacs databases, using the terms “Nurses,” “Postoperative Care,” “Cardiac Surgery,” and “Intensive Care Unit”. The results obtained in the nine articles studied show that nurses, because they are in direct contact with patients at their bedsides, are responsible for performing various invasive procedures, constantly monitoring vital signs, and being alert to various complications that may arise. In addition, there are several challenges faced by the profession during this period, which require the use of care strategies to improve assistance. Even though more studies are needed in this area, it can be concluded that nurses play a fundamental role in this process, as they can use different tools to establish individualized treatment plans focused on the needs of each individual. This is only possible with training and a continuous educational process.